Pelaksanaan Bimbingan Pranikah Remaja Usia Sekolah dengan Pendekatan Al Hikmah (Studi Kasus di Kecamatan Pahandut Kota Palangka Raya) - Annisa Annisa; Desi Erawati; Arini Safitri; Muhammad Ansori (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Different issues facing school-age adolescents at today's age include teenage sexual abuse, sex outside of marriage, deviant sexual behavior, undesirable pregnancies, and early marriage. The guidance of school-age teenagers is one of the government’s efforts to save teenagers from falling down the wrong path. This study aims to analyze the implementation of the guidance of school-age youth with the use of the al-hikmah approach. The research method use is qualitative-descriptive. Data is collected using interviews and documentation, which is subsequently analyzed using an al-hikmah approach based on aspects such as selection of sources, methods of submission of materials, selection of materials, and content of materials. The informants in this study are five people consisting of sources and committees involved in the activities of guidance for school-age adolescents, namely religious teachers, leaders, marriage practitioners, and officials of the Religious Affairs Office (KUA) in Pahandut. The results of this study showed that the implementation of school adolescent wedding guidance in Pahandut district faced several obstacles, namely: time constraints, a lack of certified facilitators who have ever followed technical guidance, and the fact that they could only reach a few schools. In the al-Wismah approach, some aspects have been matched.